Diversity, composition, and role of woody Non-Timber Forest Products in Tawangmangu, Central Java, Indonesia (Asian Journal of Ethnobiology, 2024)
Abstract. Haqqin F, Arkan F, Ibriza NM, Fadhilah RN, Safira RN, Dewangga A, Kusumaningrum L, Thenya T, Setyawan AD. 2024. Diversity, composition, and role of woody Non-Timber Forest Products in Tawangmangu, Central Java, Indonesia. Asian J Ethnobiol 7: 68-78. Forests have an important role in supporting biodiversity and providing various ecosystem services vital for human welfare; besides that, forests are also an important resource for Non-Timber Forest Products (NTFP), which are forest products other than timber used by local communities. NTFP can be categorized into fodder, firewood, food wrapping, medicinal plants, ornamental plants, spices, and food. The aim of this research was to analyze biodiversity and the use of NTFP in the villages of Plumbon, Nglebak, and Sepanjang, located in Tawangmangu Sub-district, Karanganyar District, Central Java, Indonesia. Data collection included interviews and field surveys. In the course of the interviews, a total of 62 respondents were engaged. The results showed that 83 plant species belonging to 41 families had been identified for many NTFPs such as (i) medicinal plant, (ii) food, (iii) ornamental plant, (iv) fodder, (v) spices; (vi) firewood; and (vii) food wrapping. The research findings indicate that Plumbon Village (Station A) exhibited the highest NTFP woody plant biodiversity value, with the highest values for each index component, i.e., 2.8 (H'), 5.9 (Dmg), and 0.765 (E). Each village is characterized by distinct dominant plant species: Melastoma malabatrichum dominates Plumbon Village (Station A), Manihot esculenta dominates Nglebak  Village (Station B), and Calliandra houstoniana dominates Sepanjang Village (Station C). Notably, the plant with the highest use value is Tectona grandis, which serves as a medicinal plant, firewood, and food wrapping material. This research provides a deeper understanding of the biodiversity and use of NTFPs in the region, which has important implications for natural resource management and the well-being of local communities.
Keywords: Forest, NTFP, plants, Tawangmangu, woody